Interannual variability of thermal state of the cold subsurface layer in the Okhotsk Sea - Vladimir A. Luchin; Vladimir I. Matveev (Известия ТИНРО, 2016)
Long-term variability of the cold subsurface water (CSW) in the Okhotsk Sea is analyzed on the base of all available oceanographic data collected in March through August of 1946-2015 (total 65,742 stations). The Integral Heat Content (IHC) is calculated for each station and average annual IHC anomalies of the cold subsurface water are determined by month and by 2-degree grid. The IHC anomaly series are analyzed using the EOF analysis. Cycles with period of approximately 30 years are revealed in the variations of the subsurface layer heat content. Thus, in the 1946-1950, its temperature decreased, but it grew since 2009-2010 to 2015. The warming of CSW was also observed in the 1951-1964 and 1978-1994, while the cooling was in the 1965-1977 and 1995-2008. Based on this criterion, the CSW thermal condition in certain years is classified as «extremely cold» in 2001, as «cold» in 1949, 1950, 1951, 1958, 1959, 1960, 1966, 1967, 1969, 1973, 1976, 1977, 1978, 1980, 1999, 2000, 2010, 2012, as «normal» in 1946, 1952, 1953, 1954, 1955, 1957, 1961, 1962, 1965, 1970, 1971, 1972, 1975, 1979, 1982, 1983, 1985, 1986, 1988, 1989, 1990, 1993, 1995, 1996, 1998, 2002, 2003, 2004, 2005, 2006, 2007, 2008, 2009, 2011, 2013, 2014, as «warm» in 1948, 1956, 1964, 1968, 1974, 1981, 1984, 1987, 1991, 1992, 1994, 1997, 2015, and as «extremely warm» in 1963. Statistically significant correlation is found between changes of the CSW thermal conditions and long-term variations of atmosphere and ocean climate indices, as well as local patterns of the atmosphere-ice-ocean interaction in the Okhotsk Sea and adjacent onshore and offshore areas of Asia and the Pacific Ocean.